2017
DOI: 10.1038/nature22044
|View full text |Cite
|
Sign up to set email alerts
|

Antisense oligonucleotide therapy for spinocerebellar ataxia type 2

Abstract: There are no disease-modifying treatments for adult human neurodegenerative diseases. Here we test RNA-targeted therapies in two mouse models of spinocerebellar ataxia type 2 (SCA2), an autosomal dominant polyglutamine disease. Both models recreate the progressive adult-onset dysfunction and degeneration of a neuronal network that are seen in patients, including decreased firing frequency of cerebellar Purkinje cells and a decline in motor function. We developed a potential therapy directed at the ATXN2 gene b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
222
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 283 publications
(245 citation statements)
references
References 31 publications
8
222
1
5
Order By: Relevance
“…Importantly, sustained ASO-5 exposure was not accompanied by evidence of induced gliosis or apoptosis in vulnerable brain regions, and no adverse events were observed even at the highest ASO doses. These results further support the growing evidence from preclinical animal and human clinical ASO trials demonstrating sustained, widespread, and well-tolerated ASO delivery to the CNS following longitudinal ICV or intrathecal delivery 20,22 . In support of the tolerability of ASOs for SCA3, recent elegant work from Toonen et al, assessed exon-skipping of the CAG repeat containing exon 10 in ATXN3 18 .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Importantly, sustained ASO-5 exposure was not accompanied by evidence of induced gliosis or apoptosis in vulnerable brain regions, and no adverse events were observed even at the highest ASO doses. These results further support the growing evidence from preclinical animal and human clinical ASO trials demonstrating sustained, widespread, and well-tolerated ASO delivery to the CNS following longitudinal ICV or intrathecal delivery 20,22 . In support of the tolerability of ASOs for SCA3, recent elegant work from Toonen et al, assessed exon-skipping of the CAG repeat containing exon 10 in ATXN3 18 .…”
Section: Discussionsupporting
confidence: 80%
“…Although the molecular mechanism causing slowed firing in Q84/WT mice was not explored here, previous experiments have suggested that impairment of K v 3 family potassium channels in this mouse model 25 contribute to spiking abnormalities, and Purkinje neurons from K v 3.3 knockout mice show slower firing and a deeper AHP 45 . Moreover, the rescue of motor impairment through pharmacologic targeting of ion channels in SCA1 mice 46 and ASO treatment in SCA2 mice 22 is associated with normalizing of Purkinje neuron firing frequency, suggesting that ASO treatment in SCA3 mice improves Purkinje neuron physiology in a behaviorally relevant manner. That said, the neural circuitry underlying motor activity is far more complex than simply the regulation of Purkinje neuron firing.…”
Section: Discussionmentioning
confidence: 99%
“…Both ASOs were developed and synthesized by Ionis Pharmaceuticals. ASOs were synthesized as described 26 and were 20 bp in length, with five 2â€Č- O -methoxyethyl (MOE) modified nucleotides at each end of the oligonucleotide, and ten DNA nucleotides in the center. The backbone of the ASOs consists of a mixture of phosphorothioate (PS) and phosphodiester (PO) linkages: 1-PS, 4-PO, 10-PS, 2-PO and 2-PS (5â€Č to 3â€Č).…”
Section: Methodsmentioning
confidence: 99%
“…We screened a collection of ASOs for safety and efficacy (Extended Data Fig. 7 and 26 ), and used the most effective and well-tolerated ASO for further studies. Intracerebroventricular (ICV) injection of 4 ÎŒg of the Atxn2 ASO at P1 did not affect the home-cage behavior or grip strength of WT mice (Extended Data Fig.…”
mentioning
confidence: 99%
“…A reduction of ataxin-2 expression by the anti-sense oligonucleotide (ASO) therapy can be a promising future therapeutic approach for the disease. This ASO has been tested in SCA2 mouse models and improved motor performance and Purkinje cells firing rate of the animals 3 . In recent years, many therapeutic attempts have been developed to repair or replace the abnormal protein generated by the genetic mutation.…”
mentioning
confidence: 99%